2017
DOI: 10.4155/fmc-2017-0110
|View full text |Cite
|
Sign up to set email alerts
|

Friend or Foe? Mitochondria as a Pharmacological Target in Cancer Treatment

Abstract: Mitochondria have acquired numerous functions over the course of evolution, such as those involved in controlling energy production, cellular metabolism, cell survival, apoptosis and autophagy within host cells. Tumor cells can develop defects in mitochondrial function, presenting a potential strategy for designing selective anticancer therapies. Therefore, cancer has been the main focus of recent research to uncover possible mitochondrial targets for therapeutic benefit. This comprehensive review covers not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 98 publications
0
26
0
1
Order By: Relevance
“…As an energy-dependent process, a distinctive feature of apoptosis is the interference of normal mitochondrial function, and mitochondria-dependent intrinsic signaling pathways are recognized as a component of apoptosis 3 , hence targeting mitochondria in cancer cells has been considered as an attractive therapeutic strategy 4,5 . Compromised mitochondrial (trans)membrane potential (ΔΨm) and its collapse lead to the opening of mitochondrial permeability transition pores, and the subsequent release of cytochrome C in the cytosol, which in turn initiates penultimate downstream events in the apoptotic cascade of caspases.…”
Section: Introductionmentioning
confidence: 99%
“…As an energy-dependent process, a distinctive feature of apoptosis is the interference of normal mitochondrial function, and mitochondria-dependent intrinsic signaling pathways are recognized as a component of apoptosis 3 , hence targeting mitochondria in cancer cells has been considered as an attractive therapeutic strategy 4,5 . Compromised mitochondrial (trans)membrane potential (ΔΨm) and its collapse lead to the opening of mitochondrial permeability transition pores, and the subsequent release of cytochrome C in the cytosol, which in turn initiates penultimate downstream events in the apoptotic cascade of caspases.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic reprogramming in cancer cells was originally attributed to impaired mitochondrial activity but can occur by other means such as increased glycolytic enzyme expression following oncogene activation. Cancer cells can be induced to return to oxidative phosphorylation, and targeting mitochondria with this goal is being actively explored as a new approach to cancer therapy [60]. Accumulative data have shown that the metabolic switch towards aerobic glycolysis and lactate production represents an advantage for tumor development and invasion, and might be the result of clonal selection in progressive malignancies.…”
Section: Resultsmentioning
confidence: 99%
“…тенденцию большинства раковых клеток производить энергию преимущественно с помощью анаэробного гликолиза с последующим образованием молочной кислоты [42]. Во многих исследованиях показано, что усиление продукции АКМ митохондриями активирует аутофагию [58], индуцирует выход ионов кальция из митохондрий и эндоплазматического ретикулума [46], посредством окисления киназы ASK1 (apoptosis signaling kinase 1) ингибирует апоптоз [35], повышает радио-и химиорезистентность опухолевых клеток [34]. Одним из важных механизмов уменьшения содержания митохондрий и генерации АКМ является митофагия.…”
Section: • -unclassified